2014
DOI: 10.2131/jts.39.293
|View full text |Cite
|
Sign up to set email alerts
|

An RNA synthesis inhibition assay for detecting toxic substances using click chemistry

Abstract: -Biological risk assessment studies of chemical substances that induce DNA lesions have been primarily based on the action of DNA polymerases during replication. However, DNA lesions interfere not only with replication, but also with transcription. There is no simple method for the detection of the DNA lesion-induced inhibition of transcription. Here, we report an assay for estimating the toxicity of chemical substances by visualizing transcription in mammalian cells using nucleotide analog 5-ethynyluridine (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previously, we demonstrated that our in vivo method for visualizing transcription in mammalian cells can detect UV- and/or chemically (e.g., camptothecin, etoposide, 4NQO, cisplatin) induced damage in genomic DNA by inhibiting RNA polymerase during transcription elongation [ 20 , 22 , 23 ]. Here, we modified this in vivo method to establish a new in vitro method (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that our in vivo method for visualizing transcription in mammalian cells can detect UV- and/or chemically (e.g., camptothecin, etoposide, 4NQO, cisplatin) induced damage in genomic DNA by inhibiting RNA polymerase during transcription elongation [ 20 , 22 , 23 ]. Here, we modified this in vivo method to establish a new in vitro method (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we established a method for detecting the effects of chemically induced DNA damage on transcription using the nucleotide analog 5-bromouridine and a anti-5-bromouridine antibody and/or the nucleotide analog 5-ethynyluridine [ 20 ] and a click chemistry reaction [ 21 , 22 ] without radioisotopes [ 23 ]. Our method is based on a model for transcription-coupled nucleotide excision repair (NER) triggered by blocked transcription at DNA lesions [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…RNA labeling has seen extensive use in imaging of infection by RNA viruses (e.g., 58 ). Another interesting application of RNA imaging has been to monitor transcription and this has been used, for example, to determine the toxicity of certain substances that inhibit transcription 59 .…”
Section: Conclusion: Current Applications and Outlookmentioning
confidence: 99%